A Field Evaluation of Construction Workers' Activity, Hydration Status, and Heat Strain in the Extreme Summer Heat of Saudi Arabia. Issue 5 (27th March 2020) - Al-Bouwarthan, Mohammed; Quinn, Margaret M; Kriebel, David; Wegman, David H
Abstract: Objectives: Assess the impact of summer heat exposure (June–September) on residential construction workers in Al-Ahsa, Saudi Arabia by evaluating (i) heart rate (HR) responses, hydration status, and physical workload among workers in indoor and outdoor construction settings, (ii) factors related to physiological responses to work in hot conditions, and (iii) how well wet-bulb globe temperature-based occupational exposure limits (WBGTOELs ) predict measures of heat strain. Methods: Twenty-three construction workers (plasterers, tilers, and laborers) contributed 260 person-days of monitoring. Workload energy expenditure, HR, fluid intake, and pre- and postshift urine specific gravity (USG) were measured. Indoor and outdoor heat exposures (WBGT) were measured continuously and a WBGTOEL was calculated. The effects of heat exposure and workload on heart rate reserve (HRR), a measure of cardiovascular strain, were examined with linear mixed models. A metric called 'heat stress exceedance' (HSE) was constructed to summarize whether the environmental heat exposure (WBGT) exceeded the heat stress exposure limit (WBGTOEL ). The sensitivity and specificity of the HSE as a predictor of cardiovascular strain (HRR ≥30%) were determined. Results: The WBGTOEL was exceeded frequently, on 63 person-days indoors (44%) and 91(78%) outdoors. High-risk HRR occurred on 26 and 36 person-days indoors and outdoors, respectively. The HSE metric showed higher sensitivity for HRR ≥30% outdoors (89%) than indoors (58%) and greater specificity indoors (59%) than outdoors (27%). Workload intensity was generally moderate, with light intensity work more common outdoors. The ability to self-pace work was associated with a lower frequency of HRR ≥30%. USG concentrations indicated that workers began and ended their shifts dehydrated (USG ≥1.020). Conclusions: Construction work where WBGTOEL is commonly exceeded poses health risks. The ability of workers to self-pace may help reduce risks.